EVALUASI EFEKTIVITAS SISTEM INFORMASI MANAJEMEN DAN AKUNTANSI BARANG MILIK NEGARA ( SIMAK-BMN ) DI DEPARTEMEN KEBUDAYAAN DAN PARIWISATA REPUBLIK INDONESIA - Anggita Kiki Rahardiyanti; Edi Abdurachman (Bina Nusantara University, 2012)
The Government obligate to secure BMN. The security include physical security, administrative, and legal secure. In order to secure the necessary administrative administration system that can create a control (controlling) on BMN. Thus the necessary tools in the form of system that can simplify the administration and control of BMN. Management Information Systems and Accounting State Assets (SIMAK-BMN) was organized with the aim to produce the necessary information as a tool of accountability for the implementation of the budget and management / control BMN controlled by an accounting unit of goods. But until now has not carried out an evaluation of the level of keefektivitas SIMAK-BMN especially in the Ministry of Culture and Tourism. Therefore conducted a study to determine the factors that influence the effectiveness of SIMAK-BMN. So this study can be useful for applications maker SIMAK-BMN in knowing what the important factors that must be considered to improve the effectiveness of SIMAK-BMN which have been implemented. The result is that the factors that influence the effectiveness of SIMAK-BMN are Facility, Usability and Quality Systems. Without the factors above, it is very unlikely that SIMAK-BMN can operate effectively.